Von Willebrand Factor in Cultured Human Vascular Endothelial Cells from Adult and Umbilical Cord Arteries and Veins - Wachem, Pauline B van; Reinders, Jan Hendrik; Buul-Wortelboer, Marijke F van; Groot, Philip G de; Aken, Willem G van; Mourik, Jan A van (Thrombosis and Haemostasis, 1986)
Endothelial cells were cultured from various human arteries and veins, obtained from adult individuals and from umbilical cords. We compared the storage and secretion of von Willebrand factor by endothelial cells from umbilical veins with that of endothelial cells cultured from a number of adult vessels, including aorta, arteria iliaca, vena saphena magna and vena cava. There were no differences in the way the cultured endothelial cells handled the von Willebrand factor they synthesized. Endothelial cells from the various vessels responded to stimuli in secreting stored von Willebrand factor. The cells also responded to thrombin and ionophore A23187 in producing enhanced amounts of prostacyclin. Thus, cultured umbilical vein endothelial cells have properties that are very similar to those of cultured endothelial cells of various other origins. It is concluded that foetal venous cells provide a representative model for studies of endothelial cell von Willebrand factor biosynthesis and prostacyclin production.
Keywords: (Human) Endothelial cells; von Willebrand factor; Prostacyclin